Mitochondrial DNA methylation in metabolic associated fatty liver disease - Archibold Mposhi; Archibold Mposhi; Fabian Cortés-Mancera; Fabian Cortés-Mancera; Janette Heegsma; Vincent E. de Meijer; Bart van de Sluis; Svenja Sydor; Svenja Sydor; Lars P. Bechmann; Lars P. Bechmann; Claudia Theys; et al. (Frontiers in Nutrition, 2023)
IntroductionHepatic lipid accumulation and mitochondrial dysfunction are hallmarks of metabolic associated fatty liver disease (MAFLD), yet molecular parameters underlying MAFLD progression are not well understood. Differential methylation within the mitochondrial DNA (mtDNA) has been suggested to be associated with dysfunctional mitochondria, also during progression to Metabolic Steatohepatitis (MeSH). This study further investigates whether mtDNA methylation is associated with hepatic lipid accumulation and MAFLD.MethodsHepG2 cells were constructed to stably express mitochondria-targeted viral and prokaryotic cytosine DNA methyltransferases (mtM.CviPI or mtM.SssI for GpC or CpG methylation, respectively). A catalytically inactive variant (mtM.CviPI-Mut) was constructed as a control. Mouse and human patients’ samples were also investigated. mtDNA methylation was assessed by pyro- or nanopore sequencing.Results and discussionDifferentially induced mtDNA hypermethylation impaired mitochondrial gene expression and metabolic activity in HepG2-mtM.CviPI and HepG2-mtM.SssI cells and was associated with increased lipid accumulation, when compared to the controls. To test whether lipid accumulation causes mtDNA methylation, HepG2 cells were subjected to 1 or 2 weeks of fatty acid treatment, but no clear differences in mtDNA methylation were detected. In contrast, hepatic Nd6 mitochondrial gene body cytosine methylation and Nd6 gene expression were increased in mice fed a high-fat high cholesterol diet (HFC for 6 or 20 weeks), when compared to controls, while mtDNA content was unchanged. For patients with simple steatosis, a higher ND6 methylation was confirmed using Methylation Specific PCR, but no additional distinctive cytosines could be identified using pyrosequencing. This study warrants further investigation into a role for mtDNA methylation in promoting mitochondrial dysfunction and impaired lipid metabolism in MAFLD.